Strength and power thresholds to identify high and low linear sprint speed performers in collegiate American football players - Philipp, N. M.; Crawford, D. A.; Cabarkapa, D.; Fry, A. C. (The Journal of Strength and Conditioning Research, 2024)
Lower-body strength and power are commonly measured performance qualities across a number of sports. In recent years, more attention has been given to relationships, primarily between lower-body strength and linear speed performance. While still limited, evidence is in agreement that lower-body strength positively contributes to linear speed performance. However, what is less well understood is if there comes a point in an athlete's development, at which, further working on increasing maximal strength may not fully compliment additional gains in speed performance. Within this study, authors aimed to provide practitioners with lower-body strength and power thresholds that can discriminate between slow and fast performers, within a group of collegiate American football players. The sample was further divided into a high-body and low-body weight group, and authors hypothesized that by using logistic regression, supplemented with receiver operator curve analyses, optimal cut-off points (i.e., relative lower-body strength thresholds) that are able to significantly discriminate between slow and fast linear speed performers may be identified. Findings indicate that optimal cut-off scores differed between the groups of athletes, as well as the lower body strength and power tests. All models were able to significantly distinguish between slower and faster performers, and area under the curve values ranged from 0.695 to 0.903. Although thresholds will likely vary based on factors such as sex, training age, and sport, findings from this investigation may be used to benchmark athletes and to further individualize training aimed at improving linear speed performance.